Thermoregulation of Meningococcal fHbp, an Important Virulence Factor and Vaccine Antigen, Is Mediated by Anti-ribosomal Binding Site Sequences in the Open Reading Frame. - Edmund Loh; Hayley Lavender; Felicia Tan; Alexander Tracy; Christoph M Tang (PLoS Pathogens)
During colonisation of the upper respiratory tract, bacteria are exposed to gradients of temperatures. Neisseria meningitidis is often present in the nasopharynx of healthy individuals, yet can occasionally cause severe disseminated disease. The meningococcus can evade the human complement system using a range of strategies that include recruitment of the negative complement regulator, factor H (CFH) via factor H binding protein (fHbp). We have shown previously that fHbp levels are influenced by the ambient temperature, with more fHbp produced at higher temperatures (i.e. at 37°C compared with 30°C). Here we further characterise the mechanisms underlying thermoregulation of fHbp, which occurs gradually over a physiologically relevant range of temperatures. We show that fHbp thermoregulation is not dependent on the promoters governing transcription of the bi- or mono-cistronic fHbp mRNA, or on meningococcal specific transcription factors. Instead, fHbp thermoregulation requires sequences located in the translated region of the mono-cistronic fHbp mRNA. Site-directed mutagenesis demonstrated that two anti-ribosomal binding sequences within the coding region of the fHbp transcript are involved in fHbp thermoregulation. Our results shed further light on mechanisms underlying the control of the production of this important virulence factor and vaccine antigen.